Discharge after stroke: Evaluation of callback data. Issue 4 (July 2019) - Carrillo-Gutierrez, Cristina; Jaime, Frances; Smith, Kim; Elsehety, Marwah; Headley, Janelle; Sostand, Shanequa; Harrison, Nicole; Strug, Polina; Vu, Kim; Savitz, Sean; Sharrief, Anjail
Abstract : Stroke patients are at increased risk for cognitive impairments and physical limitations after discharge. Enhancing the discharge process can help drive improved outcomes. Abstract : Stroke patients are at increased risk for cognitive impairments and physical limitations after discharge. Enhancing the discharge process can help drive improved outcomes.